Management of an Underground River to Overcome Water Scarcity in the Gunung Sewu Karst Area, Indonesia - Choirul Amin; Priyono Priyono; Arif Jauhari; Yuli Priyana; Kuswaji Dwi Priyono; Munawar Cholil (Forum Geografi, 2017)
Since people living in a karst area periodically face a crisis due to a lack of fresh water, it is necessary to re-evaluate the ability to use water resources. An appropriate and effective management is required to use available water resource sustainably. We describe a management process of exploring underground river in karst region as water resources. The activities completed included four phases, namely exploration, pre-lifting activities, the water lifting and post-lifting activities. The exploration phase included speleological surveys and data collection for the cave mouth using remote sensing instrument. The pre-lifting was done to prepare various requirements before the lifting process was completed. The water lifting phase consisted of the construction of an underground river dam, the installation of submersible pumps, the construction of reservoirs and the installation of piping to connect to the public hydrant. The post-lifting phase was mainly conducted to organise water distribution evenly. This management model was evidenced to successfully overcome drought in Pucung village by providing fresh water to the local community. Moreover, this model promoted residents’ cost savings by reducing their expenses for buying water from IDR 50,000/m3 to IDR 3,500/m3 (1,300 percent).